2007
DOI: 10.1039/b708760h
|View full text |Cite
|
Sign up to set email alerts
|

Superacid promoted reactions of N-acyliminium salts and evidence for the involvement of superelectrophiles

Abstract: Experimental and theoretical studies suggest the involvement of dicationic, superelectrophilic N-acyliminium ions in conversions catalyzed by superacids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Calculations have shown a large energetic effect in the protosolvation of an N-acylimium ion (140) and its reaction with benzene ( Figure 29). [51] For the calculated gas-phase reactions (MP2/6-311+G(d) level), formation of the s-complex 142 is found to be somewhat endothermic for the monocationic electrophile 140, and strongly exothemic for the dicationic superlectrophile (141). The favorable energetics can be explained by the separation of charge in the s-complex 143, a process that is driven by charge-charge repulsion.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Calculations have shown a large energetic effect in the protosolvation of an N-acylimium ion (140) and its reaction with benzene ( Figure 29). [51] For the calculated gas-phase reactions (MP2/6-311+G(d) level), formation of the s-complex 142 is found to be somewhat endothermic for the monocationic electrophile 140, and strongly exothemic for the dicationic superlectrophile (141). The favorable energetics can be explained by the separation of charge in the s-complex 143, a process that is driven by charge-charge repulsion.…”
mentioning
confidence: 97%
“…[15] In the case of g-diketones, such as 2,5-hexanedione (50), the heats of diprotonation are found to be about 5 kcal mol À1 less that expected, when compared to the twice the heat of protonation of acetone and other monoketones ( Figure 11). The decreased heat of diprotonation is a consequence of the Coulombic destabilization of the dicationic structure (51). With increasing separation of the carbonyl groups in the diketones (52, n = 3), the heats of diprotonation are about equal to twice the heats of protonation of monoketones.…”
mentioning
confidence: 98%
“…Extensive NMR analysis of the crude reaction mixture resulting from the treatment of this substrate, for which any cationic trapping with the o , o ′‐difluorinated aromatic ring must be avoided, provided strong evidence for the formation of the N ‐acyl iminium ion Au (C−H iminium proton at δ =8.41 ppm and C−H carbon atom at δ =191.7 ppm) . This species is also characterized by an amide carbonyl group slightly deshielded to 172.5 ppm in the 13 C NMR spectrum and a ketone carbonyl group slightly shielded to 195.8 ppm, respectively compared to an average of 167.5 ppm and 202.5 ppm for products 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Extensive NMR analysis of the crude reaction mixture resulting from the treatment of this substrate,f or which any cationic trapping with the o,o'-difluorinated aromatic ring must be avoided, provided strong evidence for the formation of the N-acyl iminium ion Au (CÀHi minium proton at d = 8.41 ppm and CÀHc arbon atom at d = 191.7 ppm). [40] This species is also characterized by an amide carbonyl group slightly deshielded to 172.5 ppm in the 13 CNMR spectrum and ak etone carbonyl group slightly shielded to 195.8 ppm, respectively compared to an average of 167.5 ppm and 202.5 ppm for products 4.Insolution, ion Au is concomitantly generated with its precursor ion Bu arising from substrate 13 CNMR spectra of asolution of substrate 3u in neat TfOH at À20 8 8C. B) Generation and 1 Ha nd 13 CNMR spectra of ion Cu generated in TfOH at À20 8 8C, revealing the absence of formation of the N-acyl iminium ion from enamide 10 u.…”
Section: Methodsmentioning
confidence: 99%
“…Reimann et al 332 have performed the stereoselective ring closing of the diastereomeric mixture of piperidinols 101 and isolated the product ergoline with a C/D cis configuration in low yield [Eq. 338 It was shown that para-dimethoxybenzene, a stronger nucleophile, is able to react in CF 3 COOH, whereas the deactivated aromatic para-dichlorobenzene is unreactive. It was also observed, however, that one of the isomers afforded the product quantitatively under identical conditions, whereas the other slowly decomposed.…”
Section: Alkylation Of Aromatic Hydrocarbonsmentioning
confidence: 99%